Heterobiografija, hipokritika in etika avtorske odgovornosti - Boldrini, Lucia (Primerjalna književnost, 2009)
Arguing that "heterobiography" (fictional autobiographies of historical individuals) places the subject at the centre of complex relationships between the historical, the fictional, the critical, the legal and the ethical, this article discusses some of the crucial questions that these texts raise.
Keywords: De Man, Paul, 1919-1983; literarna teorija; literary theory; avtor; avtorstvo; smrt avtorja; avtobiografska literatura; heterobiografija; avtorska odgovornost